2022
DOI: 10.3390/agronomy12081821
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Elevation and Nitrogen Supply Alter the Growth and Physiological Responses of Tomato and Barley Plants to Drought Stress

Abstract: Global climate change will modify plants in terms of growth and physiology. To better understand the consequences of this effect, the responses of the leaf water relations and nitrogen (N) use efficiency of barley and tomato plants to elevated CO2 (e[CO2], 800 ppm) combined with progressive drought stress at two levels of N supply (N1, 0.5 g N pot−1 and N2, 1.0 g N pot−1) were studied. The plants were grown in two separate phytotrons at ambient CO2 (a[CO2], 400 ppm) and e[CO2], respectively. The leaf physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…In elevated CO 2 concentrations, positive correlations were observed between ShDW with GW, LA, and DPPH under normal and water stress and negative correlations with APX. This suggests that increased shoot dry weight is associated with higher levels of leaf pigments, larger leaf size, enhanced antioxidant activity, and enzymatic defense mechanisms [7,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In elevated CO 2 concentrations, positive correlations were observed between ShDW with GW, LA, and DPPH under normal and water stress and negative correlations with APX. This suggests that increased shoot dry weight is associated with higher levels of leaf pigments, larger leaf size, enhanced antioxidant activity, and enzymatic defense mechanisms [7,40].…”
Section: Discussionmentioning
confidence: 99%
“…Ainsworth and Rogers [37] reported increased biomass and grain yield in barley under elevated CO 2 . Additionally, elevated CO 2 has enhanced photosynthetic performance and increased carotenoid content in various plant species [7]. The increase in Fv/Fm suggests improved photosynthetic capacity and light energy utilization under elevated CO 2 conditions [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a key factor influencing CO 2 uptake by plants [ 101 ]. It is intimately linked with photosynthetic and water use efficiency, especially under drought-stress conditions [ 102 ]. In this study, the sensitive wheat cultivar Shandawel 1 showed a substantial decrease in gs under DS.…”
Section: Discussionmentioning
confidence: 99%